Regulasi Hak Kekayaan Komunal dalam Hukum Internasional dan Hukum Indonesia: Tantangan dan Solusi - Azzahra, Mariam Alifa (Veteran Law Review, 2025)
Communal property rights are a cornerstone of sustainable resource management and the preservation of indigenous cultures and traditions. These rights guarantee fair access and long-term sustainability by enabling communities to cooperatively own, use, and manage resources. A framework for ensuring the protection and advancement of these rights is offered by international agreements like the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP). In Indonesia, the Constitution and important laws, such as Law No. 5/1960 on Basic Agrarian Principles, promote the recognition of communal property rights under hak ulayat. However, there are still major obstacles in the way of putting these rights into practice. These include disputes between corporate interests and communal land claims, the absence of official recognition for many indigenous communities, and the difficulties between sustainable resource governance and national development ambitions. The legal frameworks governing community property rights at the national and international levels are examined in this article, along with important issues and potential fixes. In order to guarantee the fair and sustainable management of shared resources, it makes the case for greater legal recognition, participatory governance, and improved cooperation between domestic and foreign parties.